2020
DOI: 10.1103/physreva.101.012114
|View full text |Cite
|
Sign up to set email alerts
|

Quantum master equations for a system interacting with a quantum gas in the low-density limit and for the semiclassical collision model

Abstract: A quantum system interacting with a diluted gas experiences the irreversible dynamics. The corresponding master equation can be derived within two different approaches: the fully quantum description in the low-density limit and the semiclassical collision model, where the motion of gas particles is classical whereas their internal degrees of freedom are quantum. The two approaches have been extensively studied in the literature but their predictions have not been compared. This is mainly due to a fact that the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 63 publications
(115 reference statements)
0
13
0
Order By: Relevance
“…65 We will consider unitary AA collisions, yet the property can be extended to non-unitary collisions (as those in Section 8.2). 66 At variance with Section 8.1, here we explicitly show the S-dependence of SA collision unitaries, which facilitates establishing the connection with the notation used for introducing composite CMs.…”
Section: Mapping Ancilla-ancilla Collisions Into a Composite Collisio...mentioning
confidence: 97%
See 1 more Smart Citation
“…65 We will consider unitary AA collisions, yet the property can be extended to non-unitary collisions (as those in Section 8.2). 66 At variance with Section 8.1, here we explicitly show the S-dependence of SA collision unitaries, which facilitates establishing the connection with the notation used for introducing composite CMs.…”
Section: Mapping Ancilla-ancilla Collisions Into a Composite Collisio...mentioning
confidence: 97%
“…Ref. [66] showed that this is equivalent to the low-density, fast-particle limit of a fully quantum treatment.…”
Section: Equations Of Motion: State Of the Artmentioning
confidence: 99%
“…If the measurement repetition rate is much greater than the maximum Bohr frequency of H , then one can neglect the term in Equation ( 13 ). This means that the system evolution in between the measurement acts is infinitesimal, so that the stroboscopic time is quasi-continuous in full analogy with the quantum collision models [ 48 , 49 , 50 , 51 ]. As a result, we obtain and the resulting non-Hermitian Hamiltonian, effectively acting on S , under the Zeno experimental protocol for repeated measurements on the ancilla, may be taken as …”
Section: Non-hermitian Hamiltonians Due To Repeated Measurementsmentioning
confidence: 99%
“…Equation ( 19 ). Therefore, the physical dynamics of are governed by the non-Hermitian Hamiltonian , which reads as follows on a conventional eigenbasis of operator : The obtained Hamiltonian provides an adequate description within the stroboscopic approximation, which is justified if [ 48 , 49 , 50 , 51 ]. However, the quantity can be comparable with if the coupling strength .…”
Section: Non-hermitian Dynamics For Coupled Qubits Induced By Repementioning
confidence: 99%
“…Note that there is also another direction in studying properties of quantum systems when one takes the large time limit together with small coupling or small density limit, see [15,16,17].…”
Section: Introductionmentioning
confidence: 99%